Situating Scientific Literacy within the Context of a Pandemic - Adarlo, Genejane M (Archīum Ateneo, 2023)
Society has increasingly looked upon science education to prepare the public for Industrial Revolution 4.0, as scientific reasoning and practices can hone 21st century skills, including scientific literacy. However, the COVID-19 pandemic has changed how science is taught and learned. Hence, this mixed methods study seeks to determine if there would be a significant increase in scientific literacy among undergraduate students after taking a six-week online course offered during the first year of the pandemic as part of their science education. It also aims to examine which aspects of the course offering students attributed, if any, their scientific literacy. Using a one-tailed paired sample t-test (α = 0.05) to compare the Global Scientific Literacy Questionnaire scores of 67 undergraduate students surveyed at the start and end of the online course, this study demonstrated a significant increase in their scientific literacy despite the constraints brought by the pandemic (p = 0.03). Specifically, these students became better at systematic thinking and information management (p = 0.01) as well as self-directed planning and monitoring (p = 0.02). A focus group discussion with five students revealed that course design and the nature of remote learning could explain the gain in their scientific literacy.